ADM: una Arquitectura Distribuida Multitarea - Martinez, Alejandro Daniel (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1987)
Nowdays, the multi-microprocessor architectures are used in computer fields like robotics and artificial intelligence.